Febrile Seizure: Demographic Features and Causative Factors - ESMAILI GOURABI, Hamed; BIDABADI, Elham; CHERAGHALIPOUR, Fatemeh; AARABI, Yasaman; SALAMAT, Fatemeh (Iranian Journal of Child Neurology, 2013)
How to cite this article: Esmaili Gourabi H, Bidabadi E, Cheraghalipour F, Aarabi Y, Salamat F. Febrile Seizure: Demographic Features and Causative Factors. Iran J Child Neurol Autumn 2012; 6(4):33-37. Abstract Objective Because of geographical and periodical variation, we prompted to determine the demographic features and causative factors for febrile seizure in Rasht. Materials & Methods In this cross-sectional study, all 6–month- to 6-year-old children with the diagnosis of febrile seizure admitted to 17 Shahrivar hospital in Rasht, from August, 2009 to August, 2010 were studied. Age, sex, family history of the disease, seizure types, body temperature upon admission and infectious causes of the fever were recorded. All statistical analysis was performed with SPSS software, version 16. Results Of the 214 children (mean age, 25.24±15.40 months), 124 were boys and 109 had a positive family history. Complex seizures were seen in 39 cases. In patients with a complex febrile seizure, 59% had the repetitive type, 20.5% had the focal type and 20.5% had more than 15 minutes duration of seizures. Most of the repetitive seizures (78.3%) occurred in patients under 2 years old; the difference between under and over 2-year-old patients was statistically significant (P=0.02). Study results did not show significant differences between the two genders for simple or complex seizures. The mean body temperature upon admission was 38.2±1.32◦C (38.31±0.82 degrees in boys and 38.04±1.78 in girls). Upper respiratory infections were seen in most patients (74.29%). All cases of lower respiratory infections were boys. There was a statistically significant difference between boys and girls in causes of fever. Conclusion Most of the children had a positive family history and the most common causative factor was upper respiratory infection. References: Huang MC, Huang CC, Thomas K. Febrile convulsions: development and validation of a questionnaire to measure parental knowledge, attitudes, concerns and practices. J Formos Med Assoc. 2006 Jan;105(1):38-48. Vaswani RK, Dharaskar PG, Kulkarni S, Ghosh K. Iron deficiency as a risk factor for first febrile seizure. Indian Pediatr. 2010 May;47(5):437-9. Sadleir LG, Scheffer IE. Febrile seizures. BMJ. 2007 Feb;334(7588):307-11. Mohebbi MR, Holden KR, Butler IJ. FIRST: a practical approach to the causes and management of febrile seizures. J Child Neurol. 2008 Dec;23(12):1484-9. Salehi Omran M, Khalilian E, Mehdipour E et al. Febrile seizures in North Iranian children: Epidemiology and clinical feature. J Pediatr Neurol. 2008;6(1):39-42. Bidabadi E, Mashouf M. Association between iron deficiency anemia and first febrile convulsion. A case-control study. Seizure. 2009 Jun;18(5):347-51. Vahidnia F, Eskenazi B, Jewell N. Maternal smoking, alcohol drinking, and febrile convulsion. Seizure. 2008 Jun;17(4):320-6. Ashrafzade F, Hashemzadeh A, Malek A. Acute otitis Media in Children with Febrile Convulsion. Iran J Otorhinolaryngol. 2002;16(35):33-9. Millichap JJ, Gordon Millichap J. Methods of investigation and management of infections causing febrile seizures. Pediatr Neurol. 2008 Dec;39(6):381-6. Hosseini Nasab A, Dai pariz M, Alidousti K. Demographic characteristics and predisposing factors of febrile seizures in children admitted to Hospital No. 1 of Kerman University of Medical Sciences. J Med Counc Islam Repub Iran. 2006;24(2):107-12. Keller A, Saucier D, Sheerin A, Yager J. Febrile convulsions affect ultrasonic vocalizations in the rat pup. Epilepsy Behav. 2004 Oct;5(5):649-54. Ogihara M, Shirakawa S, Miyajima T, Takekuma K, Hoshika A. Diurnal variation in febrile convulsions. Pediatr Neurol. 2010 Jun;42(6):409-12. Fallah R, Akhavan S, Mir Sadat Nasseri F. Clinical and demographic characteristics of first febrile seizure in children. J Shaeed Sdoughi Uni Med Sci Yazd. 2009;16(5):61-5. Khodapanahande F, VahidHarandi N, Esmaeli F. Evaluation of seasonal variation and circadian rhythm of febrile seizures in children admitted to the pediatric ward of Rasoul-e-Akram hospital. Razi J Med Sci. 2008;15(59):59-66. Hassanpour onje H, Ghofrani M, Taheri N. Risk factors of recurrent febrile seizures in children admitted to hospital with the children of Hazrat Ali Asghar. J Iran Uni Med Sci. 2006;16(65):46-54. Habib Z, Akram S, Ibrahim S, Hasan B. Febrile seizures: factors affecting risk of recurrence in Pakistani children presenting at the Aga Khan University Hospital. J Pak Med Assoc. 2003 Jan;53(11):11-7. Abaskhanian A, Vahid Shahi K, Parvinnejad N. The Association between Iron Deficiency and the First Episode of Febrile Seizure. J Babol Univ Med Sci. 2009;11(3):32-6. Mahyar A, Ayazi P, Fallahi M, Javadi A. Risk factors of the first febrile seizures in Iranian children. Int J Pediatr. 2010 2010:862897. Kolahi AA, Tahmooreszadeh S. First febrile convulsions: inquiry about the knowledge, attitudes and concerns of the patients’ mothers. Eur J Pediatr. 2009 Feb;168(2):167-71. Talebian A, Honarpishe A, Mohajeri S, et al. Risk factors associated with incidence of first febrile seizure in children. Faiz. 2003;7(2):55-8. Sanaee Dashty A, Akhlaghi AK, Pazoki R. Clinical risk factors of febrile seizure in children in a university hospital in Bushehr port. Iranian south medical journal (Teb-e-Jonoob). 2007;9(2):168-74. Golestan M, Fallah R, Akhavan S. Evaluation of CSF in 100 children admitted with febrile seizures. J Shaeed Sadoughi Uni Med Sci Yazd. 2009;16(5):3-7.